Using Tensiometers for Vegetable Irrigation Scheduling in Miami-Dade County - Teresa Olczyk; Yuncong Li; Rafael Munoz-Carpena (EDIS)
This document is Fact Sheet ABE 326, one of a series of the Department of Agricultural and Biological Engineering, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: August 2002.